A NOTE ON THE MISINTERPRETATION OF SECTION 13 OF THE TRUST PROPERTY CONTROL ACT: A PROPOSED SOLUTION - Latiefa Manie (Obiter, 2018)
Section 13 of the Trust Property Control Act (57 of 1988 hereinafter “the TPCA”) has received much judicial attention in recent times. Several applications in terms of section 13 of the TPCA related to amending a trust provision contained in a charitable bequest which allegedly conflicted with constitutional principles. Consequently, section 13 attained a constitutional dimension. The judgments can be commended for the manner in which our courts have attempted to strike a balance between the various constitutional rights at stake in such matters. However, the note will reveal that our courts have at times misinterpreted the criterion of section 13 in its attempt to address the constitutional arguments put forth. The note will highlight the content and depth of section 13. Thereafter, the focus will shift to the constitutional dimension attained by the provision with particular reference to charitable trusts, followed by a discussion of the manner in which the provision has been interpreted by our courts. The aim of the note is to provide a workable solution that will give effect to the method in which the provision is currently being interpreted and strike a balance between the constitutional rights at play.